2015
DOI: 10.1097/sla.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biological Sex in Severely Traumatized Patients on Outcomes

Abstract: Males are more susceptible to multiple organ failure, sepsis, and mortality after trauma. Differences were not exclusively related to reproductive age and thus cannot be attributed to sex hormones alone. Females aged 16 to 44 years seem to tolerate shock better. Higher susceptibility to sepsis might be explained by male immune function or increased systemic burden from higher rates of surgical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 52 publications
(139 reference statements)
2
46
0
Order By: Relevance
“…This more florid organ failure response by severely injured males is similar to previous findings as described by Sperry and others. (2, 5) While overall nosocomial infection rates were not different, ventilator associated pneumonia rates were significantly higher in males as opposed to females, which also has been shown in previous reports. (21-23) Additionally, our model interaction analysis suggested that male gender may confer greater risk of 28-day mortality, but not prolonged organ dysfunction, in patients receiving massive transfusion amounts of blood products in the first 12 hours.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This more florid organ failure response by severely injured males is similar to previous findings as described by Sperry and others. (2, 5) While overall nosocomial infection rates were not different, ventilator associated pneumonia rates were significantly higher in males as opposed to females, which also has been shown in previous reports. (21-23) Additionally, our model interaction analysis suggested that male gender may confer greater risk of 28-day mortality, but not prolonged organ dysfunction, in patients receiving massive transfusion amounts of blood products in the first 12 hours.…”
Section: Discussionsupporting
confidence: 81%
“…Within these studies, there have been many reports of improved clinical outcomes for females as compared to males after severe traumatic injury. (1-5) However, published data remains conflicting on the magnitude and significance of these differences. (6-9) Results from varying animal models suggest that estrogen and testosterone influence the physiologic, immunologic and organ system responses to traumatic injury.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been hypothesized to tolerate shock to a greater extent and have a lower susceptibility to sepsis [55]. Seven studies in the systematic review independently identified males as having statistically elevated rates of mortality after spine surgery and similar results are apparent in other disciplines such as trauma surgery [56]. These facts, combined with the reduced between-study heterogeneity and absence of publication bias for the works included in our analysis, lend further support to our findings.…”
Section: Discussionsupporting
confidence: 75%
“…The pooled OR estimate in the meta-analysis maintained a 63% increase in postoperative odds of death for males compared with females. This may be reflective of underlying physiologic differences between the sexes as well as variation in the number and severity of medical comorbidities [45,46,56,58]. Females are known to have lower rates of coronary artery disease, peripheral vascular disease, and renal dysfunction [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation